BERPIKIR INTUITIF SEBAGAI SOLUSI MENGATASI RENDAHNYA PRESTASI BELAJAR MATEMATIKA - Sofia Sa'o (Program Studi Pendidikan Matematika, 2018)
Mathematics as a field of study often complained of the difficult and tedious because they containnumbers and formulas in pembelajaranya thus leads to lower student achievement. Tjuan of this study was todescribe the solution in addressing the lack of achievement of learning mathematics with an intuitive way ofthinking. The method used is qualitative descriptive method to describe solutions that silakukan intuitive thinkingsubject. The low mathematics achievement by Soedjadi (2006) that can be sourced from within the students andoutside students. One important factor to achieve the goal of education is the thought process that made the studentsduring the learning of mathematics in progress. The thought process that used one of them is to think intuitively.Intuitive thinking is a cognitive process that led to the idea as a strategy for making decisions resulting inspontaneous answers in solving problems. Spontaneous answer is both written and oral expression, resulting personof solving math problems without using the analytic way of thinking.